2023
DOI: 10.1177/00315125231213167
|View full text |Cite
|
Sign up to set email alerts
|

Motor Processing in Children With Cochlear Implants as Assessed by Functional Near-Infrared Spectroscopy

Razieh Alemi,
Jace Wolfe,
Sara Neumann
et al.

Abstract: Auditory-motor and visual-motor networks are often coupled in daily activities, such as when listening to music and dancing; but these networks are known to be highly malleable as a function of sensory input. Thus, congenital deafness may modify neural activities within the connections between the motor, auditory, and visual cortices. Here, we investigated whether the cortical responses of children with cochlear implants (CI) to a simple and repetitive motor task would differ from that of children with typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…These studies suggest a cross-modal reorganization or The precentral gyrus, which contains many giant pyramidal cells, is the center of body movement in humans and an important structure for executing voluntary movements (48). Previous studies have confirmed that in infants, language ability is acquired by learning the connection between pronunciation and movements through sound stimulation (49), which indicates that the synchronous coordination of functions between the auditory cortex and the motor cortex may be an important factor in language development (50). Recent studies have shown that children with severe SNHL have no significant changes in the visual cortex, but there are significant changes in connections between the auditory cortex and the somatosensory and sensorimotor cortices (23).…”
Section: Changes In Alff and Reho In The Auditory Cortex Visual Corte...mentioning
confidence: 87%
“…These studies suggest a cross-modal reorganization or The precentral gyrus, which contains many giant pyramidal cells, is the center of body movement in humans and an important structure for executing voluntary movements (48). Previous studies have confirmed that in infants, language ability is acquired by learning the connection between pronunciation and movements through sound stimulation (49), which indicates that the synchronous coordination of functions between the auditory cortex and the motor cortex may be an important factor in language development (50). Recent studies have shown that children with severe SNHL have no significant changes in the visual cortex, but there are significant changes in connections between the auditory cortex and the somatosensory and sensorimotor cortices (23).…”
Section: Changes In Alff and Reho In The Auditory Cortex Visual Corte...mentioning
confidence: 87%
“…Continuous fNIRS was recorded using 39 LED sources and 31 detectors from the NIRScout system developed by ‘NIRx Medical Technologies’ (LLC, USA), whose theoretical montage was shown in Alemi et al . 54 Each source emitted near-infrared light at two wavelengths 760 and 850 nm. An ‘EasyCap’ (Easycap GmbH, Germany) was used to hold the sources and detectors, and their position was registered with three fiducials (nasion and left/right pre-auricular point) and later digitized using the ‘FieldTrip’ toolbox.…”
Section: Methodsmentioning
confidence: 99%
“…The data from the two imaging techniques were acquired sequentially, with counterbalanced order. Several other tasks were conducted using the same techniques in each child on the same day: a low-level auditory task, 56 a motor task, 54 a phonological task (spoken/written words and pseudo-words), an audiovisual integration task, 57 emotional processing (a 10-min child-friendly video from the movie ‘Despicable Me’) and a 7-min resting-state recording. 58 As the entire protocol for each technique was substantial, they were conducted at different times with a large break in between.…”
Section: Methodsmentioning
confidence: 99%